Financial Ratio Analysis and Du Pont System to Evaluate the Financial Performance of PTBA And ITMG - Ahmad Zulaihan; Siti Rizka Fauziyah (P2M Politeknik Pertanian Negeri Samarinda, 2023)
The research was conducted to analyze the financial performance of coal subsector energy sector companies, including PT Bukit Asam (Tbk) and PT Indo Tambangarya Megah (Tbk), with financial ratio analysis and Du Pont System. This study used balance sheet and income statement data from 2019 to 2022 from both companies and conducted financial ratio analysis on liquidity, activity, profitability, solvency, and with the Du Pont System. The results of the financial ratio analysis show that both companies have experienced an increase in the current ratio over the past four years, with a more significant increase occurring in ITMG. However, PTBA experienced fluctuations in the current ratio value. Both companies also experienced an increase in cash ratio in 2020. In addition, the total asset turnover ratio decreased in 2020 due to the Covid-19 pandemic, but in 2021 it increased due to increased production. The financial performance of the two companies is generally quite good with stable and good ratio values in the profitability ratio. Both companies also have good solvency ratios, with relatively low Debt to Equity Ratio (DER) and Debt to Asset Ratio. From the Du Pont analysis, in general, the performance of PT ITMG compared to PTBA is relatively better in terms of ROE and ROI Du Pont.